WGCNA analysis reveals hub genes in the Hemarthria compressa roots in response to waterlogging stress - Wenwen Li; Xiaoli Zhou; Minghao Qu; Yuqian Zheng; Bingna Shen; Bing Zeng; Yanlong Feng; Kaiyue Pang; Jiahai Wu; Bing Zeng (Scientific Reports)
Abstract Hemarthria compressa is a high-quality forage resource in China. In recent years, waterlogging has frequently occurred, adversely affecting the growth and development of H. compressa. In order to investigate the physiological and molecular response mechanisms of H. compressa under waterlogging stress and identify hub genes involved in waterlogging tolerance, H. compressa roots from the GY (waterlogging-tolerant) and N1291 (waterlogging-sensitive) cultivars were selected as experimental materials in this study. The physiological indexes of H. compressa were measured, and transcriptome sequencing was carried out after 8 h and 24 h of waterlogging stress, with 0 h used as the control group. Superoxide dismutase (SOD) and peroxidase (POD) activities were significantly increased in both GY and N1291 under waterlogging stress (P < 0.05). Weighted gene co-expression network analysis (WGCNA) identified a total of four modules significantly associated with waterlogging stress (r>|0.9|, P < 0.05). Gene ontology (GO) and Kyoto encyclopedia of genes and genomes (KEGG) enrichment results showed that differentially expressed genes (DEGs) were mainly enriched in the Starch and sucrose metabolism, Plant hormone signal transduction, Ribosome and Glutathione metabolism pathways. Seven hub genes were also retrieved, including Cluster-38255.67514 and Cluster-38255.80127, potentially associated with waterlogging tolerance. It is related to the Ribosome pathway and participates in the process of anti-waterlogging regulation. The results of this experiment provide new insights into the response mechanisms of H. compressa to waterlogging stress and a theoretical framework for the effective selection and breeding of waterlogging-tolerant cultivars.